Designing educational systems to support enactment of the Next Generation Science Standards. Issue 7 (17th July 2018) - Anderson, Charles W.; de los Santos, Elizabeth X.; Bodbyl, Sarah; Covitt, Beth A.; Edwards, Kirsten D.; Hancock, James Brian; Lin, Qinyun; Morrison Thomas, Christie; Penuel, William R.; Welch, Mary Margaret
Abstract: This article reports on a design‐based implementation research (DBIR) project that addresses the question: How can classrooms be supported at scale to achieve the three‐dimensional learning goals of the Next Generation Science Standards? Inherent in this question are three key design challenges: (i) three‐dimensional learning— the multidimensional changes in curriculum, assessment, and instruction required for three‐dimensional learning; (ii) scale— the necessity of change at multiple scales in educational systems; and (iii) diversity— achieving rigor in our expectations with responsiveness to the enduring diversity of our students, classrooms, and schools. We discuss findings from the Carbon TIME project, which focuses on teaching carbon cycling and energy transformations at multiple scales. Findings focus on design and knowledge building in three interconnected contexts. (i) Assessment— understanding and assessing students' three‐dimensional learning. Learning progression frameworks provide insight into students' reasoning and the basis for efficient and reliable classroom and large‐scale assessments that have used automated scoring of constructed responses for over 80, 000 tests. (ii) Classrooms— classroom discourse and learning communities. Six Carbon TIME units are based on an instructional model that scaffolds students' engagement with phenomena as questioners, investigators, and explainers. The units support substantial learning and reduce the achievement gap between high‐pretest and low‐pretest students, but with substantial differences among teachers. (iii) Professional communities— a professional development course of study and research‐practice partnerships address issues of organizational resources, conflicting norms and obligations, and building practical knowledge in schools and districts. Project results show continuing advantages for schools with more organizational resources. Overall, results provide evidence that it is possible to measure and achieve three‐dimensional learning at scale. However, this accomplishment requires substantial investments in the material, human, and social resources of educational communities of practice.